1989
DOI: 10.1111/j.1365-2311.1989.tb00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the 7‐spot and 2‐spot ladybird beetles (Coccinellidae) in their toxic effects on a bird predator

Abstract: ABSTRACT. 1. Experiments with nestling blue tits Parus caeruleus L.examined the effects of feeding them 7-spot ladybird Coccinella septempunctata (L.), 2-spot ladybird Adalia bipunctata (L.) or controls Tenebrio sp.2. A feeding rate of 5'/i 7-spot ladybirds per day 'killed' nestlings within 2 days. Three of six nestlings fed at half this rate survived 4 days. In contrast, all experimental birds survived sixty-four 2-spot ladybirds fed over 4 days (equivalent by weight to the high 7-spot diet).3. Nestlings fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 9 publications
(16 reference statements)
0
77
1
Order By: Relevance
“…All the birds had encountered and learned to eat 'control' beetles Alphitobhu diaper inus (a dark brown palatable beetle, comparable in size to a ladybird), and mealworms, Tenebrio molitor, and had learned to avoid seven-spot ladybirds over at least three encounters about 2 months before the experiment began. Forty-nine of the birds had also experienced both typical and melanic forms of the two-spot ladybird, Adalia bipunctata, which is mildly distasteful but not toxic (Marples et al 1989), and learned to eat or avoid them. Birds from each breeding stock, sex and two-spot ladybird experience were distributed as evenly as possible across all treatments to minimize the effects of these parameters on the results…”
Section: The Japanese Quailmentioning
confidence: 99%
See 1 more Smart Citation
“…All the birds had encountered and learned to eat 'control' beetles Alphitobhu diaper inus (a dark brown palatable beetle, comparable in size to a ladybird), and mealworms, Tenebrio molitor, and had learned to avoid seven-spot ladybirds over at least three encounters about 2 months before the experiment began. Forty-nine of the birds had also experienced both typical and melanic forms of the two-spot ladybird, Adalia bipunctata, which is mildly distasteful but not toxic (Marples et al 1989), and learned to eat or avoid them. Birds from each breeding stock, sex and two-spot ladybird experience were distributed as evenly as possible across all treatments to minimize the effects of these parameters on the results…”
Section: The Japanese Quailmentioning
confidence: 99%
“…nestlings (Marples et al 1989) and contains two alkaloids, coccinelline and its free base precoccinelline (Pasteels et al 1973), which taste bitter. The alkaloid is distributed throughout the body of the adult seven-spot ladybird, but is more concentrated in the reflex blood that exudes from the tibia/femur joint of the legs, when the ladybird is attacked (Kay et al 1969;Holloway et al 1991).…”
mentioning
confidence: 99%
“…However, the water extract of crushed whole eggs is likely to contain the species specific alkaloids that are known to be present in ladybird eggs (Pasteels et al 1973). Some of these alkaloids are known to be toxic to vertebrates (Frazer & Rothschild 1960;Marples et al 1989) and therefore it does not seem unreasonable to assume they are responsible for the toxicity of ladybird eggs. Starving adults of Menochilus sexmaculatus (F.) and Coccinella trans6er-salis (F.) both consume their own eggs more readily than those of the other species, and C. trans6ersalis is more reluctant to eat the eggs of M. sexmaculatus than 6ice 6ersa (Agarwala et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…These chemicals are correlated with color properties in some species (Blount et al, 2012). Several studies have suggested that ladybird color patterns, and overall appearance, are important for predator detection (Marples et al, 1989(Marples et al, , 1994Dolenská et al, 2009). However, only recently Blount et al (2012) considered the actual role of avian visual sensitivity in their results.…”
Section: Introductionmentioning
confidence: 99%